Maintenance of S. aureus in Co-culture With P. aeruginosa While Growing as Biofilms - Woods, Paul W.; Haynes, Zane M.; Mina, Elin G.; Marques, Cláudia N. H. (Frontiers in Microbiology, 2019)
Bacterial biofilms are found in various environmental niches and are mostly comprised by two or more bacterial species. One such example, are the mixed species bacterial biofilms found in chronic lung infections of cystic fibrosis (CF) patients, which include the Staphylococcus aureus and Pseudomonas aeruginosa bacterial species. S. aureus is one of the CF lung initial colonizers and is assumed to be abrogated when P. aeruginosa becomes established, eliminating its involvement as the infection evolves. Common models used in research do not mimic the actual progression of the mixed species biofilms thus, in this work we developed an in vitro model, where S. aureus biofilms establish prior to the introduction of P. aeruginosa, simulating a state that is phenotypically more similar to the one found in CF lungs. Overall our results demonstrate that S. aureus is not outcompeted, and that timing of inoculation and bacterial concentration affect the final bacterial ratio and quorum sensing related gene expression during the dual species biofilm development.